MicroRNAs in Platelet Physiology and Function - Lindsay, Cory R.; Edelstein, Leonard C. (Seminars in Thrombosis and Hemostasis, 2016)
Platelets are anucleate blood cells that are best known for their role in hemostasis and thrombosis. Perhaps due to the necessity of maintaining a proteome over an 8- to 9-day lifespan or the need to adapt to environmental situations, platelets retain many of the RNA metabolic processes of nucleated cells such as the ability to splice, translate, and regulate RNA levels through posttranscriptional mechanisms. In fact, in the absence of transcription, the dependence on posttranscriptional mechanisms to regulate gene expression may have resulted in microRNAs (miRNAs) making up a greater proportion of the platelet transcriptome than observed in other cells. miRNAs are ∼22 nucleotide RNA molecules that regulate gene expression through messenger RNA (mRNA) degradation or inhibition of translation. miRNAs regulate differentiation of the platelet precursor, the megakaryocyte. Identification of miRNA:mRNA pairs that are associated with platelet phenotypes has led to the discovery of novel regulators of platelet function in healthy and diseased subjects. Circulating miRNAs may originate from platelets and can serve as biomarkers for platelet function. Platelet microparticles have been demonstrated to have the ability to deliver miRNAs of extracellular targets and alter gene expression in those targets. This review summarizes the current state of knowledge of miRNAs in megakaryocytes, platelets, and platelet microparticles.
Keywords: platelets; megakaryocytes; microRNA; microparticles